(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
According to the calculated data of our researchers, from 3 to 10% of the population suffers from occlusive diseases of the arteries of the lower extremities, increasing to 15-20% among patients older than 70 years [1,3]. A third of patients with critical lower limb ischemia develop critical ischemia 6-8 years after the appearance of the first signs of the disease. According to some epidemiological studies, the incidence of peripheral artery diseases in patients with diabetes ranges from 10 to 40%, and in the presence of ulcerative foot defects reaches 50% [4,5]. In Uzbekistan, chronic ischemia of the lower extremities has been diagnosed in more than one hundred thousand people. Vascular atherosclerosis is the cause of chronic lower limb ischemia in 80-90% of cases. This pathology is especially often observed in people over 60 years of age[2].